2023
DOI: 10.3390/bioengineering10070848
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Oral Disease-Modifying Treatment Effects on Cognitive Outcomes in Multiple Sclerosis: A Scoping Review

Abstract: Introduction. Cognitive impairment represents one of the most hidden and disabling clinical aspects of multiple sclerosis (MS). In this regard, the major challenges are represented by the need for a comprehensive and standardised cognitive evaluation of each patient, both at disease onset and during follow-up, and by the lack of clear-cut data on the effects of treatments. In the present review, we summarize the current evidence on the effects of the available oral disease-modifying treatments (DMTs) on cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Previous studies that have carried out disease-modifying treatments (DMTs) and investigated their effects on cognition point to a benefit for cognitive performance by reducing the development of new lesions and the progression of cerebral atrophy [ 16 , 17 ]. However, new studies with DMTs have shown stability or a mild improvement in cognitive outcomes in a short-time follow-up (the duration of most studies is ≤2 years) [ 18 ]. Nevertheless, the studies do not report a standard cognitive evaluation and the placebo effect, the possible effect of other CNS drugs, and the time needed under DMTs to prevent CI are unclear in most of the observations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that have carried out disease-modifying treatments (DMTs) and investigated their effects on cognition point to a benefit for cognitive performance by reducing the development of new lesions and the progression of cerebral atrophy [ 16 , 17 ]. However, new studies with DMTs have shown stability or a mild improvement in cognitive outcomes in a short-time follow-up (the duration of most studies is ≤2 years) [ 18 ]. Nevertheless, the studies do not report a standard cognitive evaluation and the placebo effect, the possible effect of other CNS drugs, and the time needed under DMTs to prevent CI are unclear in most of the observations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, new studies with DMTs have shown stability or a mild improvement in cognitive outcomes in a short-time follow-up (the duration of most studies is ≤2 years) [ 18 ]. Nevertheless, the studies do not report a standard cognitive evaluation and the placebo effect, the possible effect of other CNS drugs, and the time needed under DMTs to prevent CI are unclear in most of the observations [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%